2023
DOI: 10.1002/smll.202206244
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Stability, Biocompatibility, and Magnetization of Suspensions of Isolated Bacterial Magnetosomes

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/smll.202206244.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…In DLS measurements, an increased overall particle diameter was measured (75.4 ± 10.9 nm), which can be explained by the formation of a hydration shell in aqueous environments. The determined zeta potential of the particles of −37.3 ± 5.4 mV is in accordance with previous analyses, 23,37 indicating a negative particle surface charge.…”
Section: ■ Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In DLS measurements, an increased overall particle diameter was measured (75.4 ± 10.9 nm), which can be explained by the formation of a hydration shell in aqueous environments. The determined zeta potential of the particles of −37.3 ± 5.4 mV is in accordance with previous analyses, 23,37 indicating a negative particle surface charge.…”
Section: ■ Resultssupporting
confidence: 91%
“…Potential cytotoxic effects of magnetosomes on the viability of mammalian cells (cancer cell lines or primary cells) have been evaluated in several studies, and dependent on the cell line tested, an overall good biocompatibility at the cell culture level has been reported . For instance, for the cancer cell lines FaDu, BeWo, and HCC78 as well as for hPC–PL primary cells we have previously demonstrated that particle amounts of up to 400 μg Fe mL –1 can be safely applied without severe effects on the cell vitality or increased cell death events. However, as the magnetosome-producing bacterial strain M. gryphiswaldense has a Gram-negative type of cell wall, which contains lipopolysaccharides (LPS) in its outer membrane, further toxicity factors have to be addressed, such as blood stability and endotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetosomes can be isolated with intact membranes; however, the latter cannot fully prevent oxidation of the magnetite cores of purified particle suspensions. Thus, even under storage conditions (HEPES buffer at 4 °C under a nitrogen atmosphere), a drop of the saturation magnetization to one-third of its initial value was observed over a period of one year [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic properties of magnetosomes (b-NPs) have been investigated in various studies [ 25 , 29 , 30 , 31 , 32 , 33 ]. Due to their particle diameters, b-NPs are near the transition range between superparamagnetic and ferrimagnetic/stable single-domain behavior (at ~30 nm).…”
Section: Resultsmentioning
confidence: 99%
“…While in terms of metallic composition, magnetosomes are characterized by the presence of an iron oxide core, in the absence of a specific treatment, some other non-metallic and non-toxic elements have been observed in small quantities (< 1.5 10 –4 % Fe per element in average) such as Na, Ca, Mg and K which could under their cationic form surround the negatively charged magnetosome surface [ 46 ]. Such impurities in the magnetosome membrane could be eliminated by removing the magnetosome membrane from the inorganic core to improve the particle purity [ 40 , 50 ].…”
Section: Discussionmentioning
confidence: 99%